Phenomenological ontology of breathing : the respiratory primacy of being - Berndtson, Petri (Abingdon, Oxon ; New York, NY : Informa Law from Routledge, 2023)
"This book studies the phenomenological ontology of breathing. It investigates breathing and air as a question of phenomenological philosophy and looks at phenomenological questions concerning respiratory methodology, ontological experience of respiration, respiratory spirituality and respiratory embodiment. Drawing on the ideas of Maurice Merleau-Ponty, Gaston Bachelard, Martin Heidegger, Edmund Husserl, Luce Irigaray and David Kleinberg-Levin, the book argues for the ontological primacy of breathing and develops a new principle of philosophy that the author calls "Silence of Breath, Abyss/Yawn of Air". It asserts that breathing is not a thing- or person-oriented relation, but perpetual communication with the immense elemental atmosphere of open and free air. This new phenomenological method of breathing offers readers a chance to begin to wonder, rethink, re-experience and reimagine all questions of life in an innovative and creative way as aerial and respiratory questions of life. Part of the Routledge Critical Perspectives on Breath and Breathing series, the book breaks new ground in phenomenology and phenomenological ontology by offering a decisive and insightful treatment of breath. It will be indispensable for students and researchers of philosophy, phenomenology, and ontology. It will also be of special interest to Merleau-Ponty scholars as it investigates uncharted dimensions of Merleau-Ponty's philosophy"--
Keywords: Ontology; Phenomenology; Respiration; PHILOSOPHY / General; PHILOSOPHY / Movements / Phenomenology